L'artisanat dans les cites antiques de l'Algérie : (Ier siècle avant notre ère - VIIe siècle après notre ère) - Amraoui, Touatia, (Archaeopress Roman archaeology ;, 2017)
This text examines the artisans of ancient North Africa as its core subject. Focusing on urban production in Algeria during Antiquity, this critical study brings together new documentation drawn up on the basis of field data and the consultation of archives from a long history of survey in Algeria and France.